Cal. Polytechnic 1908 [baseball team] - Frank Aston::::::photographer::: (1908)
1908 baseball team, 2 different uniforms, with equipment; 17 players; in front of administration building.(Published in Polytechnic Journal (v.3, no.7, Apr. 1908) with caption 'Polytechnic Baseball Squad, 1908')